Heavy metal accumulation, chlorophyll content and stomatal density of shade plants in response to air pollution in Banda Aceh, Indonesia - MEUTIA ZAHARA; VERA NAZHIRA ARIFIN; FIRMANSYAH RACHMAN; DEWI SARTIKA ARYANI (Society for Indonesian Biodiversity, 2025)
Abstract. Zahara M, Arifin VN, Rachman F, Aryani DS. 2025. Heavy metal accumulation, chlorophyll content and stomatal density of shade plants in response to air pollution in Banda Aceh, Indonesia. Biodiversitas 26: 5449-5457. There is increasing air pollution in Banda Aceh as the number of population and vehicles are growing. This study aimed to investigate the impacts of air pollution on shade plants by measuring heavy metals (i.e. Fe, Cu, Pb) accumulation, chlorophyll content and stomatal density of the leaves. Purposive sampling was conducted to collect leaves of plants exposed to two different levels of pollution, i.e. polluted plants along the busy streets in Jambo Tape Sub-district and less polluted plants (control) in Lamsayeun Village, Ingin Jaya Sub-district. There were five plant species that dominated the surveyed streets, i.e. Tamarindus indica, Polyalthia longifolia, Pterocarpus indicus, Plumeria acuminata and Athrotaxis sp. Leaf samples of the five dominant species were brought for laboratory analysis to measure heavy metal, chlorophyll content and stomatal density with three replicates taken from different individual plants of each species. Key findings included an increase in stomatal density in the polluted plants compared to the controls with the highest observed was in P. longifolia (807.82 mm-2). Chlorophyll a, b, and total chlorophyll levels were generally lower in polluted plants compared to those as control. These findings suggest an adaptation mechanism to pollution. There was an elevated heavy metal level (Fe, Cu, Pb) in foliage, particularly in Athrotaxis plant leaves with Fe content reaching 247.2 mg/kg exceeding toxicity thresholds. The study confirmed a significant level of pollution in the area studied. These findings provide critical insights for selecting plant species in urban greening initiatives, with the potential to enhance pollution mitigation and support ecosystem health.